1958
DOI: 10.1038/bjc.1958.66
|View full text |Cite
|
Sign up to set email alerts
|

The Modifying Influence of Diet and the Physical Environment on Spontaneous Tumour Frequency in Rats

Abstract: THE unusually high frequency of phaeochromocytoma in albino Wistar strain rats bred for many years in our laboratory in Johannesburg compared with that reported from the Wistar Institute by Yeakel (1947) suggested that environmental factors among other conceivable factors were able to influence the development of spontaneous neoplasms in the albino rat (Gillman et al. 1953). It is known that diet can modify the speed of emergence of neoplasms induced experimentally by means of specific carcinogens (Rusch, 194… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1960
1960
1993
1993

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 4 publications
(3 reference statements)
2
15
0
Order By: Relevance
“…The occurrence of adrenal gland tumors was high only between 105 and 130 weeks of age, though Gilbert [7] and Gillman [8] reported high age-related incidences in Wistar-GG rats. Previous descriptions have shown that metastasis of tumors was rare in rats [5,16].…”
mentioning
confidence: 98%
“…The occurrence of adrenal gland tumors was high only between 105 and 130 weeks of age, though Gilbert [7] and Gillman [8] reported high age-related incidences in Wistar-GG rats. Previous descriptions have shown that metastasis of tumors was rare in rats [5,16].…”
mentioning
confidence: 98%
“…All (female) [5,17,18,20] ; Wistar rats, 1-60% (male), 2-69% (female) [2,3,7,9,11,12,16,26]; Fischer 344 rats, 15% or 240 (male), 36% (female) [6,21] and Brown Norway (BN/Bi) rats, 14% (male), 26% (female)…”
mentioning
confidence: 99%
“…Endometrial cancer rarely develops spontaneously in rats [11], though it can be experimentally produced in rats using polynuclear aromatic hydrocarbons (3-methylcholanthrene, DMBA) [4], In the present 24-week experi ment, no endometrial cancer was observed in rats treated with DMBA alone. This may be due to the DMBAsesame oil solution leaking out from the uterine cavity after administration.…”
Section: Discussionmentioning
confidence: 81%